Concrete strength control: ABNT, ACI and EN comparative procedures. Site study case - Helene, Paulo; Boni, Ricardo; Britez, Carlos (Revista ALCONPAT, 2018)
This paper presents an approach regarding the control of compressive strength of concrete performed by Brazilian standard, additionally was proceeded with an analysis, from the same data, performed by ACI 318-14 and EN 206. In Brazil, the control of the axial compressive strength of concrete is proceed following ABNT NBR 12655:2015. However, when this control is proceeded by other standards criteria, the results are not coincident. The ACI 318 procedures of sampling and the acceptance criteria are different from the model adopted by Brazilian standard. For this paper, a real case study was carried out, where a fck=40MPa, (SCC) has been produced, during 2 years and 9 months and poured on the building structure located in the city of São Paulo.